Frequency of Inferior Alveolar Nerve (IAN) Injury in Mandibular Fractures at Tertiary Care Hospital - Ayesha, Ayesha Yousuf; Ruqayyah Shah; Anum Mushtaq; Muzna Tahir; Saba Rizwan (Medical Journal of South Punjab, 2024)
Objective: To evaluate the frequency of inferior alveolar nerve injury in patients with mandibular fracture at tertiary care hospital.Methodology: The study was conducted in the Department of Oral and Maxillofacial Surgery at Jinnah Postgraduate Medical Centre, Karachi, from January 2024 to June 2024. Baseline information, and etiology of trauma (road traffic accident, fall, or assault), was recorded. Inferior alveolar nerve (IAN) injury involves any sensory impairment of the nerve, which can be clinically assessed by the absence of response to light touch using a Semmes-Weinstein monofilament or a camel brush.Results: The mean age was similar in both groups, 31.43±3.86 vs. 32.56±4.24, and no significant differences were found in gender distribution, with 76.6% males in the injury group vs. 80.0% in the non-injury group. Road traffic accidents (RTA) were the most common cause of IAN injury at 55.5% vs 42.0%, followed by falls 31.3% vs 32.0%, and assaults 13.3% vs 26.0%.Conclusion: The frequency of IAN is 71.9% in mandibular fractures, and there is no significant link between IAN injury and patient demographics. RTAs were the most common cause of IAN injury. Systemic factors like diabetes, hypertension, and obesity had little impact on IAN injury.